DAMPAK ORIENTASI PELANGGAN DAN INOVASI LAYANAN MELALUI KEMAMPUAN PEMASARAN DINAMIS: PENDEKATAN RESOURCE-BASED VIEW DAN TEORI KEMAMPUAN DINAMIS - Andreas; Lauw Sun Hiong (Department of Management - Institut Shanti Bhuana, 2025)
One of the problems experienced by micro, small, and medium enterprises is ignoring the importance of creating a sustainable marketing strategy and adapting to economic developments in the era of globalization. This study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis to reveal the relationship between customer orientation and dynamic capability theory, which aims to improve marketing performance in the Small and Medium Enterprise Food and Beverage sector. The population in this study consisted of MSME entrepreneurs in Pontianak city, West Kalimantan, Indonesia with a total sample size of 134 in the food and beverage business sector. The results of the analysis show that the adoption of dynamic capability theory can provide insight to business people to determine marketing strategies that are sustainable and adaptive to economic development.